'A responsible nuclear weapons power' : nuclear weapons and Indian foreign policy - Kerttunen, Mika, 1961- (Helsinki : National Defence University, 2009)
Tiivistelmä.
Väitöskirja
Keywords: ydinaseet; ulkopolitiikka; ydinasevaltiot; Intia